Blood biomarkers for dementia in Hispanic and non‐Hispanic White adults. Issue 1 (9th April 2021) - Gonzales, Mitzi M.; Short, Meghan I.; Satizabal, Claudia L.; O' Bryant, Sid; Tracy, Russel P.; Zare, Habil; Seshadri, Sudha
Abstract: Introduction: The study evaluated if blood markers reflecting diverse biological pathways differentiate clinical diagnostic groups among Hispanic and non‐Hispanic White adults. Methods: Within Hispanic (n = 1193) and non‐Hispanic White (n = 650) participants, serum total tau (t‐tau), neurofilament light (NfL), ubiquitin carboxyl‐terminal hydrolase LI, glial fibrillary acidic protein (GFAP), soluble cluster of differentiation‐14, and chitinase‐3‐like protein 1 (YKL‐40) were quantified. Mixed‐effects partial proportional odds ordinal logistic regression and linear mixed‐effects models were used to evaluate the association of biomarkers with diagnostic group and cognition, adjusting for age, sex, ethnicity, apolipoprotein E ε4, education, and site. Results: T‐tau, NfL, GFAP, and YKL‐40 discriminated between diagnostic groups (receiver operating curve: 0.647–0.873). Higher t‐tau (odds ratio [OR] = 1.671, 95% confidence interval [CI] = 1.457–1.917, P < .001), NfL (OR = 2.150, 95% CI = 1.819–2.542, P < .001), GFAP (OR = 2.283, 95% CI = 1.915–2.722, P < .001), and YKL‐40 (OR = 1.288, 95% CI = 1.125–1.475, P < .001) were associated with increased likelihood of dementia relative to cognitively unimpaired and mild cognitive impairment groups. Higher NfL was associated with poorer global cognition (β = –0.455, standard error [SE] = 0.083, P < .001), semantic fluency (β = –0.410, SE = 0.133, P = .002), attention/processing speed (β = 2.880, SE = 0.801, P < .001), and executive function (β = 5.965, SE = 2.037, P = .003). Higher GFAP was associated with poorer global cognition (β = –0.345, SE = 0.092, P = .001), learning (β = –1.426, SE = 0.359, P < .001), and memory (β = –0.890, SE = 0.266, P < .001). Higher YKL‐40 (β = –0.537, SE = 0.186, P = .004) was associated with lower memory scores. Interactions with ethnicity were observed for learning (NfL, GFAP, YKL‐40), memory (NfL, GFAP), and semantic fluency (NfL; interaction terms P < .008), which were generally no longer significant in a demographically matched subset of Hispanic and non‐Hispanic White participants. Discussion: Blood biomarkers of neuronal/axonal and glial injury differentiated between clinical diagnostic groups in a bi‐ethnic cohort of Hispanic and non‐Hispanic Whites. Our results add to the growing literature indicating that blood biomarkers may be viable tools for detecting neurodegenerative conditions and highlight the importance of validation in diverse cohorts.